2017
DOI: 10.1177/1057083717736243
|View full text |Cite
|
Sign up to set email alerts
|

Core Practices in Music Teaching: A Delphi Expert Panel Survey

Abstract: The pedagogical content knowledge framework has been used to decipher the complexities of teaching by integrating subject matter knowledge with knowledge of teaching and knowledge of learners. Researchers in math, English, and history have modified this framework to identify core teaching practices within their disciplines. Core teaching practices are those that novices can begin to master and have a direct impact on student success. We developed a preliminary list of core practices in music using a Delphi pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
3
13
0
1
Order By: Relevance
“…The Delphi (Millican & Forrester, 2018) panel's high rating for in-service teachers' developing knoweldge of and relationships with students corroborated the findings reported by Forrester (2018) in a study that examined the intersection between instrumental music teachers and conducting. Instrumental music teachers (N = 4) reported that developing and maintaining relationships was a key aspect of their practice, and this was the only intercase finding that was common across each of the participants.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…The Delphi (Millican & Forrester, 2018) panel's high rating for in-service teachers' developing knoweldge of and relationships with students corroborated the findings reported by Forrester (2018) in a study that examined the intersection between instrumental music teachers and conducting. Instrumental music teachers (N = 4) reported that developing and maintaining relationships was a key aspect of their practice, and this was the only intercase finding that was common across each of the participants.…”
supporting
confidence: 77%
“…There is a decades-long history of music education researchers examining characteristics and skills associated with effective teaching and assessing the extent to which preservice music teachers develop those competencies. Building on studies of PCK and the professional opinions of experienced music educators, researchers are now attempting to identity a body of core music teaching practices (Abramo, 2016;Ballantyne, 2006;Ballantyne & Packer, 2004;Chandler, 2012;Duling, 1992;Gohlke, 1994;Haston, 2018;Haston & Leon-Guerrero, 2008;Mateiro, Russell, & Westvall, 2012;Millican & Forrester, 2018;Venesile, 2011). The purpose of this descriptive study was to investigate how in-service music educators rated and ranked selected core music teaching practices in terms of their relative importance for beginning music teachers.…”
Section: Purpose and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…ACL experiences have been discussed in research regarding preservice preparation as an approach to improve teaching (e.g., Brophy, 2002; Conway 2012; Groulx, 2016; Roulston et al, 2005), develop pedagogical content knowledge (Ballantyne, 2007; Grieser & Hendricks, 2018; Millican, 2008), and affect teaching efficacy (Prichard, 2017). Core teaching practices, as identified by researchers such as Millican and Forrester (2017), may also provide a framework within which music teacher educators can support the development of undergraduate students’ skills that will be used in music teaching regardless of specialization. Hendricks’s (2015) review of studies on self-efficacy outlines numerous ways to develop self-efficacy in music settings and might be a foundation for practice and further research regarding the implementation of this idea.…”
Section: Discussionmentioning
confidence: 99%